2021
DOI: 10.3390/horticulturae7080256
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Enhancement of Cucumber (Cucumis sativus L.) through Optimized Use of Poultry Manure and Mineral Fertilizers under Greenhouse Cultivation

Abstract: Cucumber, a widely cultivated vegetable, is mostly grown under greenhouse conditions. In recent years, the overuse of inorganic fertilizers for higher yield attainment adversely has affected human health and the environment. Therefore, a greenhouse experiment was designed to evaluate the effects of different nutrient sources (poultry manure (PM) and mineral fertilizer (MF)) on productivity-enhancing parameters of cucumber via univariate and multivariate analyses. Amounts of PM and MF (NPK15:15:15) were added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
1
15
0
3
Order By: Relevance
“…The demand of Cucumber in the 2017 is high. The research Sallam et al (2021) state that the Cucumber is widely cultivated vegetable, mostly under the greenhouse environment. The research Kusumiyati et al (2022) the flower ratio balance affected in decrease of Cucumber harvested if the number of male flower lower than female flower.…”
Section: Mapping Commodities Production Level Of Vegetables and Fruitsmentioning
confidence: 99%
“…The demand of Cucumber in the 2017 is high. The research Sallam et al (2021) state that the Cucumber is widely cultivated vegetable, mostly under the greenhouse environment. The research Kusumiyati et al (2022) the flower ratio balance affected in decrease of Cucumber harvested if the number of male flower lower than female flower.…”
Section: Mapping Commodities Production Level Of Vegetables and Fruitsmentioning
confidence: 99%
“…Similarly, Ullah et al [20] reported that all growth parameters of vegetable plants significantly decreased with the decreased N fertilizer application, indicating the deficit in soil N supply for plant growth in vegetable fields. A further result from multivariate analyses also showed that compared with CK, N fertilizer application would be a better choice to improve cucumber growth and productivity under facility cultivation conditions [42]. Hence, it is necessary to replenish soil N supply by topdressing at a later growing stage, despite the widely reported N accumulations with the increasing years of greenhouse vegetable cultivation [16,43,44].…”
Section: Cucumber Plant Growthmentioning
confidence: 99%
“…It is rich in mineral elements, essential nutrients N, P, and K, and other nutrients that can stimulate microbial activity and healthy plants, ameliorate seed germination, increase vegetative traits, reduce the negative impact of salinity, increase the percent root colonization of arbuscular mycorrhizal fungi, improve the physical and chemical properties of the soil (structure, texture, porosity, etc. ), maintain the balance of soil nutrient, improve nutrient absorption, increase root vitality, increase fertilizer retention, enhance yields, and participate in the addition of organic matter to organically-deficient soils (Mufwanzala and Dikinya 2010;Revell et al 2012;Awad 2016;Pandian et al 2016;Sikder et al 2019;Sistani et al 2019;Solaiman et al 2020;Zhang et al 2020;Sallam et al 2021). Hirzel et al (2018) showed that the highest values of available P and exchangeable K, S, Ca and Mg were obtained using poultry manure in saline soil, whereas pH and salinity (electrical conductivity) reported the lowest values.…”
Section: Rhizophagusmentioning
confidence: 99%
“…In the other hand, salinity is among the most significant threats hindering global food security. Arbuscular mycorrhizal fungi and poultry manure (practice alone or in combination) were commonly used for agricultural production for their abilities to improve plant health to salinity stress (Solaiman et al 2020;Zhang et al 2020;Sallam et al 2021;Sofy et al 2021aSofy et al , 2021b. Arbuscular mycorrhizal (AM) fungi are among the most common soil fungi and the majority of plant species have associations with AM fungal species (Selvaraj and Chellappan 2006).…”
Section: Introductionmentioning
confidence: 99%